The Nexus Effect When Leaders Span Group Boundaries - Yip, Jeffry; Wong, Serena; Ernst, Christopher (Center for Creative Leadership, 2008)
In this age of global interconnection, leaders need to go beyond their traditional focus on managing and protecting group boundaries and work toward boundary-spanning leadership-bridging intergroup boundaries in order to achieve a shared vision or goal. The experiences of leaders in three different sectors shed some preliminary light on the collective solutions that can be achieved when leaders facilitate collaborative practices across diverse and even divided groups.